BUSINESS INVESTMENT AND REFLECTIONS ON WORKING CAPITAL MANAGEMENT - Reis, M. M. [UNESP]; Santos, D. F. L. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2017)
This work aims to understand how variations in long-term investments influence on working capital management Brazilian firms. The sample computed 255 non-financial companies with stock traded in the BM&FBOVESPA and financial data to period between 2011 to 2015. From quantitative methods by regression analysis using panel data, refuted the expectation of trade-off between liquidity and profitability, given that the investments in fixed assets positively impact the Treasury and influence the growth of Need Working Capital, which shows concern for companies to maintain liquidity. It was also found that the positive effect of investments in Fixed Assets in the Treasury and Need Working Capital reinforce the Long-term funding sources should be sufficient to ensure the Fixed Assets and the financial slack.
Keywords: Working Capital; Finance Short-term; Investment. Dynamic Model